RAILWAY CONNECTIONS OF SELECTED INTERMODAL TERMINALS IN THE CZECH REPUBLIC (Perner's Contacts, 2011)
The paper presents the current railway connections realised from selected intermodal terminals in the Czech Republic. Aim of this paper is to characterise possibilities of the container shipments tracing destined from/to Czech Republic mainly through the North Sea ports and through intermodal terminals in other countries. Existing railway transport links with Sea ports and terminals are compared in association with information about the number of connections and their frequency.
Keywords: railway connection; intermodal terminal; operator of intermodal transport